Pecalang Empowerment Model for Traditional Village Resilience in Denpasar City - Anak Agung Putu Sugiantiningsih; Anak Agung Ketut Sudiana; I Made Gede Ray Misno; I Nengah Suriata; I Made Adiwidya Yowana; Moch. Noor (International Journal of Social Science and Business, 2022)
In securing traditional villages, the existence of Pecalang is very much needed, considering that Pecalang is the guardian and strength of the Balinese people. The current socio-cultural conditions of Bali are increasingly alarming and marginalized from the growing economy and industry. In the development of the existence of traditional villages, it seems that traditional villages affect the social life of the Balinese people, for the presence of Pecalang can awaken Balinese Taksu in the eyes of the world. The purpose of this study is to explore information and implement policies for sustainability related to Pecalang in their resilience to the existence of traditional villages. This type of research is qualitative research with a descriptive approach. Methods of collecting data using surveys, interviews, and questionnaires. The process of extracting data is carried out with the snowball technique. The data analysis technique used descriptive qualitative analysis. The study results show that pecalang has indeed been proven to maintain security and order in the customary village area. Pecalang's commitment to carrying out his duties is very high. Pecalang is steadfast in their commitment to self-defense of custom, religion, and state as long as they are given the trust to carry out their duties. Pecalang organizations will be able to finance all organizational resource needs, including improving the quality of human resources to be more professional, work facilities and infrastructure, work systems and procedures, technology, and others. Thus, the organization will be better able to improve the quality of service to the demands of the customer community needs.